Picosecond Pulse Generation by Second-Order Distributed Feedback Dye Laser - Do, Hoa Quang; Duong, V.; Lien, N. T. H.; Katarkevich, V. M. (Communications in Physics, 2019)
A Configuration of a second-order distributed feedback dye laser pumped by a nanosecond Nd:YAG laser is setup. The tuning range is narrower than that in the case of the first-order DFDL but lower noise and more stable is obtained. Single picoseconds pulse tunable in range of 543 to 596 nm can be observed by using different laser dyes. The tuning range is extended to the shorter wavelengths, which is closed to pumping wavelength.